Mariko Mori. - Consey, Kevin E.; Corrin, Lisa; Eliel, Carol S.; King, Margery; Molon, Dominic; Peyton-Jones, Julia; Museum of Contemporary Art, Chicago; Serpentine Gallery, London (Chicago : Museum of Contemporary Art Chicago, 1998)
Since the early 1990s, Japanese artist Mariko Mori has emerged as one of the most imaginative and intriguing artists working with new multimedia technologies. In 1997, her pioneering 3 D video Nirvana was included in The Nordic Pavilion at the Venice Biennale. Mori, who divides her time between Tokyo and New York, is a former model whose training in fashion studies rigorously informs her investigations of the impact of media on the cultural construction of identity. Her panoramic photographs and video installations present fantastic tableaux that conflate past, present, and future and feature the artist in the roles of cyborgs or otherworldly spirits. Her recent bodies of work draw upon traditional Far Eastern spirituality and mesh Japanese popular culture, such as Japanimation and video games, with the pop culture of the West. This fully illustrated book , the first on Mori's innovating art, contextualizes her work in a series of essays by curators of four different exhibitions organized between May 1998 and March 1999 in the United States and London.
Mariko Mori, Museum of Contemporary Art, Chicago, October 10, 1998 - March 14 1999 / Serpentine Gallery, London, June 30 - August 9, 1998
bibliog. p. 86-87
biog., ind. tent., gr. tent. p. 85-86
Engels
boek
Keywords: Mori, Mariko